JAMINAN SOSIAL DAN PENAWARAN TENAGA KERJA LANJUT USIA - Ratu Eva Febriani (Ecosains: Jurnal Ilmiah Ekonomi dan Pembangunan, 2012)
Most research on labor force participation of elderly and its connection with social security program is based on macro data. This paper offers a different perspective. The research used small sample from elderly population. It is limited on education level, especially higher education (bachelor, master, and doctor) and the previous job as lecturer. This paper is using micro data from a university in Yogyakarta. It’s collected through questionnaire and interview. Using logistic regression, it is shown that health is important factor in determining the labor force of elderly decision to work, whereas social security in this case is not determining factor.